An assessment of vitamin B12 through determination of cobalt by X-ray fluorescence spectrometry. (November 2021) - Sunitha, Y.; Kumar, Sanjiv
Abstract: An X-ray fluorescence spectrometric method for the determination of vitamin B12 in vitamin formulations is described. The method is based on the measurement of Co, the only metallic constituent of vitamin B12 . The method is simple, has no spectral interference from any element except Fe and is applicable to both solid and aqueous (dissolved solids) phases. It has a limit of the detection of 2.8 μg/g for Co and 64 μg/g for vitamin B12 in solid pharmaceuticals and 2.0 μg/g for Co and 46 μg/g for vitamin B12 in the liquid (aqueous) counterparts. Several commercial vitamin tablets containing vitamin B12 in 1500–3000 μg/g range are analysed with an accuracy of ~10%. Taking advantage of the water-soluble nature of vitamin B12, some tablets have also been analysed after the ultrasonic extraction of vitamin B12 in aqueous medium. Phosphorous, another distinguishing constituent of vitamin B12, is not found suitable for determining the vitamin due to elevated background and spectral interferences. Highlights: Co is determined by XRF to measure vitamin B12 in pharmaceuticals. Cellulose is a suitable matrix for the preparation of Co containing solid standards. Interference from Fe Kβ is suitably corrected. Measurements are made on solid and also dissolved pharmaceuticals.